Management of COVID-19 Infection and Midwifery Care of a Woman with Breast Cancer - A Case Report - AydÄ±n DoÄŸan, Reyhan; HancÄ±oÄŸlu AytaÃ§, Selma (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Breast cancer is among the common cancer types in women, with an incidence of 1/3000 in pregnancy. The outbreak of the COVID-19 pandemic has not only affected society but also heightened the risk of patients with underlying conditions, especially cancer victims. The prolongation of the treatment period complicates the process that entangles breast cancer patients. In this case, the follow-up period of the patient diagnosed with breast cancer in the third trimester of their second pregnancy was discussed. The frequency of follow-up during the postpartum COVID-19 period significantly decreased, and therefore, recurrence was experienced. Consequently, it is pertinent to support cancer patients during disasters and pandemics to help keep their physical and mental health. The patients should be guided in their public health follow-ups and the frequency of examinations. Also, midwife-assisted care should be provided during these follow-ups.